The influence of product quality, service, word of mouth (WOM) and price on consumer loyalty - Evi Novitasari; Wulandari Wulandari; Zain Khiswari; Siti Nur Halimah (Journal of Business Innovation and Research, 2023)
The This study aims to determine the effect of product quality, service, Word of Mouth (WOM) , price , simultaneously on consumer loyalty . The population in this study were consumers of the Sulistio Rahayu Shop in East Sukadana Village, Sukadana District, East Lampung Regency, Lampung who had bought gamis products at the Sulistio Rahayu Shop more than twice. This research is homogeneous, where the entire population has the same opportunities for consumer loyalty . The design used in this study is a causal research design. The research method used is a qualitative research method based on post-positivism philosophy. This research uses the Cronbach's Alpha reliability test technique. The data that has been collected is processed in the form of numbers and analyzed quantitatively by testing the hypothesis with the analytical model used, namely the SPSS Statistics 26 software . The results of the statistical software data processing analysis show R 2 of 0.823 meaning that there is an influence of product quality, service, word of mouth (wom) and price on consumer loyalty at Sulistio Rahayu Stores of 82.3%, the rest is influenced by other factors. The alternative hypothesis Ha is accepted and Ho is rejected, meaning that the value of product quality is 0.055 so there is no positive and insignificant effect between product quality and consumer loyalty at Sulistio Rahayu Stores. Furthermore, the service value is 0.118, the value of word of mouth (wom) and the price value is 0.526 so that it can be said that there is a positive and significant influence between service, word of mouth (wom) and price on consumer loyalty at Sulistio Rahayu Stores.